2018
DOI: 10.1002/jpln.201700437
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of various organic matter fractions to soil–water interactions and structural stability of an agriculturally cultivated soil

Abstract: The presence and mutual interactions of soil organic matter (SOM) and clay particles are major factors determining soil structural stability. In the scope of agricultural management and environmental sustainability, it remains unclear how various mineral and organic matter (OM) fractions, OM-clay interactions and swelling processes in the interparticle space determine soil-water interactions and thus soil structural stability. To investigate this issue, we isolated the mineral and OM fractions of an agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 74 publications
(128 reference statements)
0
8
0
3
Order By: Relevance
“…Generally speaking, the research literature has found that farming households with more secure land tenure status tend to adopt more soil and water conservation land management techniques [25,29,53,54]. In our case study, however, despite the large role played by organic matter inputs in regulating soil organic carbon (SOC) and the critical role SOC plays in water capture and storage [55,56] and soil biological activity and diversity [57,58], sharecroppers appear to invest proportionately much more in chemical fertilizer inputs than manure inputs. Given the extremely arid ecological context and the much larger irrigation water inputs compared to farming households that rent land, this may indicate important sustainability concerns for sharecropping farms and provides an additional example, where enhanced land tenure status may not always lead to the adoption of more sustainable agricultural practices (such as Varble et al, 2016).…”
Section: Sharecropping As a Special Case Of More Secure Land Tenure Smentioning
confidence: 80%
“…Generally speaking, the research literature has found that farming households with more secure land tenure status tend to adopt more soil and water conservation land management techniques [25,29,53,54]. In our case study, however, despite the large role played by organic matter inputs in regulating soil organic carbon (SOC) and the critical role SOC plays in water capture and storage [55,56] and soil biological activity and diversity [57,58], sharecroppers appear to invest proportionately much more in chemical fertilizer inputs than manure inputs. Given the extremely arid ecological context and the much larger irrigation water inputs compared to farming households that rent land, this may indicate important sustainability concerns for sharecropping farms and provides an additional example, where enhanced land tenure status may not always lead to the adoption of more sustainable agricultural practices (such as Varble et al, 2016).…”
Section: Sharecropping As a Special Case Of More Secure Land Tenure Smentioning
confidence: 80%
“…biomass in ORG plots at 60-100 cm, it did increase biomass at 0-15 and 15-60 cm depths, attributed to more favorable nutrient stoichiometry for biomass formation (Kirkby et al, 2011;Richardson et al, 2014). Increased surface microbial biomass is an important potential source of C and other nutrients to subsurface layers through cell lysis from predation and wet-dry cycles (Bonkowski, 2004;Xiang et al, 2008) and is associated with increased stabilized carbon storage through microbial necromass formation (Buchmann and Schaumann, 2018;Jilling et al, 2020), contributing to the SOC increase observed in ORG systems (Figure 2b).…”
Section: Compost + Cover Crops Increased Nutrient Availability and Dementioning
confidence: 99%
“…The management of organic matter (OM) plays an important role in the productivity and sustainability of soils, both in terms of providing nutrients for crops as well as the maintenance of soil physical qualities and essential biological processes (Palm, Gachengo, Delve, Cadisch, & Giller, 2001; Wood & Bradford, 2018). Soil organic matter (SOM) is essential for promoting a range of ecosystem functions such as improved soil physical structure (Jensen et al, 2019; Sarker et al, 2018), water capture and storage (álvarez, Carral, Hernández, & Almendros, 2013; Buchmann & Schaumann, 2018), carbon (C) sequestration (Takimoto, Nair, & Nair, 2008), and the maintenance of soil biodiversity and activity (Walmsley & Cerdà, 2017).…”
Section: Introductionmentioning
confidence: 99%